J.M. Coetzee and the novel writing and politics afer Beckett - Hayes, Patrick, 1976- (Oxford English monographs., 2010)
This book argues that the significance of Coetzee's complex & finely-nuanced fiction lies in the acuity with which it both explores & developes the tradition of the novel - ranging from Cervantes, Defoe, & Richardson, to Dostoevsky, Kafka, & Becket - as part of a sustained attempt to rethink the relationship between writing & politics.